2006
DOI: 10.1007/s11259-006-3303-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Enrofloxacin and Its Metabolite Ciprofloxacin in Male and Female Turkeys following Intravenous and Oral Administration

Abstract: The pharmacokinetics of enrofloxacin (EFL) was investigated in turkeys (6 male and 6 female; 7-month-old at the start of the experiment), after intravenous and oral administration at a dose of 10 mg/kg body weight. The serum concentrations of EFL and its active metabolite ciprofloxacin (CFL) were determined by high-performance liquid chromatography. The serum concentrations vs time were analysed by a compartmental analysis. The mean values of EFL pharmacokinetic parameters showed differences only between value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…The current findings concur with the results obtained by Marien et al (2006Marien et al ( , 2007. The success of the high efficacy level of enrofloxacin is supported by several pharmacokinetic studies performed in turkeys (Heinen et al, 1997;Dimitrova et al, 2006;Fraatz et al, 2006). According to these studies, a dose of 10 mg/kg enrofloxacin given orally at 24-h intervals results in the establishment of a steady- state concentration in the serum and respiratory tract that is bactericidal for O. rhinotracheale organisms with a minimum inhibitory concentration of 0.03 mg/ml.…”
Section: Discussionsupporting
confidence: 91%
“…The current findings concur with the results obtained by Marien et al (2006Marien et al ( , 2007. The success of the high efficacy level of enrofloxacin is supported by several pharmacokinetic studies performed in turkeys (Heinen et al, 1997;Dimitrova et al, 2006;Fraatz et al, 2006). According to these studies, a dose of 10 mg/kg enrofloxacin given orally at 24-h intervals results in the establishment of a steady- state concentration in the serum and respiratory tract that is bactericidal for O. rhinotracheale organisms with a minimum inhibitory concentration of 0.03 mg/ml.…”
Section: Discussionsupporting
confidence: 91%
“…A relatively low Vd (ss) value indicates a drug that is less extensively distributed in extravascular tissues. Different pharmacokinetic studies with enrofloxacin, florfenicol and amoxicillin in either turkeys or chickens have been performed (Carceles et al ., 1995;Anadón et al ., 1996;Rios et al ., 1997;Bugyei et al ., 1999;Knoll et al ., 1999;Shen et al ., 2003;Cox et al, 2004;Switala et al ., 2004;Dimitrova et al ., 2006). From these studies, it may be concluded that the Vd (ss) value of amoxicillin (0.042 to 1.52 l/kg) is generally lower than those of florfenicol (1.5 to 4.99 l/kg) and enrofloxacin (2.92 to 3.9 l/kg).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing half-life values determined in different experiments, it may be concluded that enrofloxacin has long half-life values (Brown, 1996;Bugyei et al , 1999;Garcia Ovando et al , 1999;Knoll et al , 1999;Dimitrova et al , 2006 and that the values for florfenicol are generally lower (Afifi & El-Sooud, 1997;Shen et al , 2002Shen et al , , 2003, with the lowest half-life values noted for amoxicillin (Lashev & Pashov, 1992;Carceles et al , 1995;Anadon et al , 1996). Although both enrofloxacin and amoxicillin have good bactericidal activity, as opposed to florfenicol, which is bacteriostatic, for example, for Escherichia coli and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…At 16°C, the bioavailability of enrofl oxacin was 66.13% in this study, which was higher than the 50.82% at 10°C and the profi les studied previously. The reported 50.82% or 66.13% bioavailability of enrofl oxacin was much lower than that of quinolones in domestic animals (Hu and Feng, 1999;Zeng et al, 2003;Albarellos et al, 2005;Dimitrova et al, 2006). However, other quinolones in turbot were reported with lower bioavailabilities than the bioavailability of enrofl oxacin, such as a 27.90% bioavailability of oxolinic acid after 10 mg/kg at 16°C, and a 59% bioavailability of fl umequine after oral administration at 10 mg/kg at 18°C (Poher, 1998;Hansen and Horsberg, 1999).…”
Section: The Comparative Pharmacokinetics Of Enrofl Oxacinmentioning
confidence: 99%